The dimensions of leadership and ideology in strengthening and institutionalizing religious moderation in Muhammadiyah - Syamsul Arifin; Umiarso Umiarso; Nafik Muthohirin; Ahmad Nur Fuad (Faculty of Law, University of Muhammadiyah Malang, 2025)
This study focuses on the leadership aspect of Muhammadiyah by emphasizing the thoughts and contributions of Haidar Nashir as the Central Board of Muhammadiyah. Therefore, this study relies on written sources, especially those written by Haidar Nashir. Religious moderation is a prominent theme in Indonesia at the end of the second decade of the 2000s. Not only is it the idea of ​​a thinker or intellectual, but it has even become one of the strategic development policies in Indonesia as stated in the 2020-2024 National Medium-Term Development Plan (RPJM) prepared by the Indonesian Ministry of National Development Planning/ National Development Planning Agency (PPN/Bappenas), based on Presidential Regulation No. 18 of 2020. The Ministry of Religion, as the technical ministry in charge of religious life, has published several documents related to religious moderation. As one of the moderate Islamic religious organizations and movements, Muhammadiyah is an interesting subject of study to examine its links and continuity with the idea of ​​religious moderation. Rather than as a normative study in the field of law that uses legislation as primary material, this study seeks to reveal the substantive aspects of the religious moderation policy linked to Muhammadiyah's efforts to strengthen and institutionalize religious moderation in Muhammadiyah. The results of this study will later show that the appearance of Muhammadiyah as a moderate Islamic ideology, organization, and movement cannot be separated from the figure of the Muhammadiyah leader, who has a strong, moderate character.